2021
DOI: 10.1177/10998004211044828
|View full text |Cite
|
Sign up to set email alerts
|

Six Weeks Effects of Dynamic Neuromuscular Stabilization (DNS) Training in Obese Postpartum Women With Low Back Pain: A Randomized Controlled Trial

Abstract: Background: The worldwide prevalence of obesity and low back pain (LBP) has recently dramatically increased and is mainly indicated among postpartum women, leading to a range of adverse health consequences. Objective: This study aimed to investigate the effects of 6 weeks of Dynamic Neuromuscular Stabilization training (DNS) in obese postpartum women with LBP. Method: This was a pretest-posttest study design. The study was conducted with 40 obese postpartum women with LBP randomized to receive DNS ( n = 20) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 66 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Low back pain (LBP) is associated with disorders and disabilities in balance [ 3 , 4 ] and movement [ 5 ]. Several non-surgical treatments have been offered to help and decrease LBP, such as joint manipulation [ 2 ], acupuncture [ 6 ], traditional therapeutic exercises [ 7 , 8 ], and medication [ 9 , 10 ]. However, the small effects of these treatments indicated that effective treatment methodologies are needed to achieve a significant therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Low back pain (LBP) is associated with disorders and disabilities in balance [ 3 , 4 ] and movement [ 5 ]. Several non-surgical treatments have been offered to help and decrease LBP, such as joint manipulation [ 2 ], acupuncture [ 6 ], traditional therapeutic exercises [ 7 , 8 ], and medication [ 9 , 10 ]. However, the small effects of these treatments indicated that effective treatment methodologies are needed to achieve a significant therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Seven other studies were omitted because of the following reasons: (a) without control group (Adnan et al, 2021; Unsgaard-Tøndel et al, 2016), (b) duplicate study (Bastiaenen et al, 2004; Stuge et al, 2004), (c) review article (Sakamoto & Gamada, 2019), (d) lack of access to data (Chaudry et al, 2013), and (e) study with different population (Raza et al, 2020). 11 studies (Bastiaenen et al, 2006; Ehsani et al, 2020; ElDeeb et al, 2019; Ghavipanje et al, 2021; Gutke et al, 2010; Khorasani et al, 2020; Mens et al, 2000; Sakamoto et al, 2018; Saleh et al, 2019; Stuge et al, 2004; Teymuri et al, 2018) met our inclusion criteria and were entered in the meta-analysis (PRISMA flow diagram; Figure 1). Studies were performed in Iran ( n = 4), Netherland ( n = 2), Egypt ( n = 2), Sweden ( n = 1), Japan ( n = 1), and Norway ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Pain-related fear and avoidance behavior increase disability and diminished movement in sufferers with chronic pain (ElDeeb et al, 2019). Therefore, it can be recommended that decreased pain by stabilizing exercises may reduce fear-avoidance patterns resulting in reducing disability (George et al, 2008; Ghavipanje et al, 2021). The activation of TrA and multifidus forms a deep muscle corset, improving stiffness to the spinal and pelvic segments while movements, hence decreasing pain and improving movement patterns (ElDeeb et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations